Factors Affecting Nutritional Status Of Toddler Under The Red Line At Tambakrejo Health Center, Jombang District, Jombang District - Stianto, Mitayakuna; Fitriana , Alfira; Rahayu , Yustina (Universitas Pahlawan Tuanku Tambusai, 2023)
Health and nutrition problems are often encountered during childhood, especially the toddler period (ages 1-5 years) which can be manifested as toddlers with BGM (BawahGarisMerah) on the KMS (KartuMenujuSehat), if the toddler is below the red line on the KMS toddler is malnourished, this is known from toddlers who are weighed at the Posyandu. The purpose of this study was to determine the factors that influence nutritional status in toddlers under the red line at Puskesmas Tambakrejo Jombang District Jombang Regency. This study used descriptive research methods using questionnaires and interviews. Data obtained by distributing questionnaires to 14 respondents with total sampling technique, the research was conducted on 06 to 13 March 2023. The results showed that the factors affecting nutritional status in toddlers below the red line are food factors, namely the lack of consumption of food ingredients that contain balanced nutrition and the lack of balance between the four sub-factors in it. The results showed that the most dominant factors that caused the occurrence of toddlers with BGM were food factors and economic factors. It is expected for respondents to be able to provide food with the type of food and the number of meals in accordance with the nutritional adequacy of 1-3 years of age per day in food according to household size (URT). In order to give time and attention to their children and also check their children in the nutrition department because most of their children are the type of children who are difficult to accept food.